Flow Cytometry Assessment of CD26+ Leukemic Stem Cells in Peripheral Blood: A Simple and Rapid New Diagnostic Tool for Chronic Myeloid Leukemia. Issue 4 (3rd February 2019) - Raspadori, Donatella; Pacelli, Paola; Sicuranza, Anna; Abruzzese, Elisabetta; Iurlo, Alessandra; Cattaneo, Daniele; Gozzini, Antonella; Galimberti, Sara; Baratè, Claudia; Pregno, Patrizia; Nicolosi, Maura; Sorà, Federica; et al.
Abstract : Background: Recent investigations in chronic myeloid leukemia (CML) have focused on the identification and characterization of leukemic stem cells (LSCs). These cells reside within the CD34 + /CD38 ─ /Lin ─ fraction and score positive for CD26 (dipeptidylpeptidase IV) a marker, expressed in both bone marrow (BM) and peripheral blood (PB) samples, that discriminates CML cells from normal hematopoietic stem cells (HSCs) or from LSCs of other myeloid neoplasms. CD26 evaluation could be a useful tool to improve the identification of CML LCSs by using flow‐cytometry assay. Methods: CD26 + LSCs have been isolated from EDTA PB and BM samples of patients with leucocytosis suspected for CML. Analysis of LSCs CML has been performed by using custom‐made lyophilized pre‐titrated antibody mixture test and control tube and a CD45 + /CD34 + /CD38 − /CD26 + panel as a strict flow cytometric gating strategy. Results: The expression of CD26 on CD34 + /CD38 − population was detectable in 211/211 PB and 84/84 BM samples of subsequently confirmed BCR‐ABL + CP‐CML patients. None of the 32 samples suspicious for CML but scoring negative for circulating CD26 + LSCs were diagnosed as CML after conventional cytogenetic and molecular testing. To validate our results, we checked for PB CD26 + LSCs in patients affected by other hematological disorders and they all scored negative for CD26 expression. Conclusions: We propose flow cytometry evaluation of CD26 expression on PB CD34 + /CD38 − population as a new rapid, reproducible, and powerful diagnostic tool for the diagnosis of CML. © 2019 The Authors. Cytometry Part B: Clinical Cytometry published by Wiley Periodicals, Inc. on behalf of International Clinical Cytometry Society.